Player Dismissal and Full Time Results in the UEFA Champions League and Europa League - Arne De Meyere; Ward Vanruymbeke; Stijn Baert (Institute of Labor Economics (IZA), 2018)
This study is the first to estimate the effects of the sending-off of a player on the full time results in international club soccer. To this end, we analyse data of more than 2,000 recent games in the UEFA Champions League and UEFA Europa League. We find that when home teams receive a red card, it harms their goal scoring and victory probabilities. By contrast, a red card for away teams can have a positive, negative, or neutral effect for them, depending on the timing of the player dismissal.
Keywords: L83; J44; Z00; 330; soccer; red card; player dismissal; performance; fixed effects regressions